(untitled) (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2026)
Vitamin E plays an important role in poultry nutrition as a potent antioxidant, supports immune function, and contributes to improved carcass quality in chickens. This study aimed to evaluate the effect of vitamin E supplementation combined with increased dietary nutrient levels on carcass characteristics, non-carcass components, and the meat-to-bone ratio of IPB-D3 chickens. A total of 160 IPB-D3 chickens were used in this experiment. The study applied a 2 × 2 factorial completely randomized design with four replications, each consisting of 10 birds. The treatments included: P1E0 = basal diet based on the 2013 SNI standard; P1E1 = basal diet supplemented with 200 ppm vitamin E; P2E0 = diet containing 10% higher nutrient levels than the basal diet; and P2E1 = diet containing 10% higher nutrient levels combined with 200 ppm vitamin E. The results indicated that increasing nutrient levels by 10% significantly (p<0.05) increased carcass percentage, but reduced jejunum percentage, relative jejunum length, relative ileum length, and cecum percentage. Vitamin E supplementation significantly increased the relative length of the cecum. It can be concluded that these treatments did not negatively affect the carcass quality, commercial cuts, and meat-to-bone ratio of IPB-D3 chickens.